Предмет: Алгебра, автор: maximgarifanov

Решите
(7√3+√48-√75)*√3
(6-√5)(2+7√5)
(5√2+6√3)(6√2-5√3)
(√17-√11)(√17+√11)
(2√x-5√y)(2√x+5√y)
(√6-2)^2
(3√7-2√3)^2

Ответы

Автор ответа: wieslawlozickip5w1nd
3

a)

(7√3+√48-√75)*√3=      (7√3+√(16*3)-√(25*3)*√3  =   (7√3+4√3-5√3)*√3=  6√3*√3= 6*3=18

b)

(6-√5)(2+7√5)=   12+42√5-2√5-√5*7√5  =  12+40√5-7*5=  40√5+12-35=  =40√5-23

c)

(5√2+6√3)(6√2-5√3)=  5√2*6√2 – 5√2*5√3 +6√3*6√2 -6√3*6√3 =

=30*2 – 25√6+36√6 – 30*3=  60+11√6 -90=  11√6-30

d)

(√17-√11)(√17+√11) = 17-11 =6

e)

(2√x-5√y)(2√x+5√y)=4x-25y

f)

(√6-2)²  =  6-√6 +4=10-√6

g)

(3√7-2√3)²=    9*7-12√21+4*3 =   63-12√21 +12= 75-12√21


Похожие вопросы
Предмет: Математика, автор: ademau2787